2014
DOI: 10.14800/ics.113
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-gamma enhances phagocytosis, the production of reactive oxygen species and pro-inflammatory cytokines – implications for innate and acquired immunity.

Abstract: Neutrophils and interferon-γ (IFN-γ) are known critical components of innate and acquired immune responses.However, recent studies have demonstrated that these two immune functions are not entirely isolated. Treatment of neutrophils with IFN-γ elicits a variety of responses depending on the stimulus and on environmental conditions. In view of the physiological and pathophysiological importance of the regulatory activity of IFN-γ in neutrophil functions and the diverse, sometimes conflicting results reported, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The precise role of IFN-γ in health is complex, since it has an important role in the control of inflammation, ranging from the migration of leukocytes to the activation of its effector function (Rauch et al, 2013). It also stimulates the production of reactive oxygen species and inflammatory cytokines (Marchi, 2014). A recent study showed an association between reduced IFN-γ and increased HDL-cholesterol levels in elderly women enrolled in an exercise program (Nishida et al, 2015), which pointed to the beneficial effect of physical training on lipid profile associated with the reduction of circulating IFN-γ.…”
Section: Discussionmentioning
confidence: 99%
“…The precise role of IFN-γ in health is complex, since it has an important role in the control of inflammation, ranging from the migration of leukocytes to the activation of its effector function (Rauch et al, 2013). It also stimulates the production of reactive oxygen species and inflammatory cytokines (Marchi, 2014). A recent study showed an association between reduced IFN-γ and increased HDL-cholesterol levels in elderly women enrolled in an exercise program (Nishida et al, 2015), which pointed to the beneficial effect of physical training on lipid profile associated with the reduction of circulating IFN-γ.…”
Section: Discussionmentioning
confidence: 99%